1999
DOI: 10.1093/tropej/45.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory study of Kala-azar in children in Nepal

Abstract: Reports are scanty regarding kala-azar in children in Nepal. In this communication we document 20 children diagnosed to have kala-azar who were admitted and treated at B. P. Koirala Institute of Health Sciences, Dharan, Nepal. The children were between 2 and 14 years old. The duration of illness varied between 12 days and 24 months with a majority (65 per cent) of children being ill for less than 6 months. Hepatomegaly and splenomegaly were seen in 95 and 90 per cent of cases respectively. Splenomegaly was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
8
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
5
8
0
4
Order By: Relevance
“…Positive findings like pallor, splenomegaly, hepatomegaly were observed but less common than to the Dash S et al 7 and Hamid GA et al 18 Visceral leishmaniasis should be strongly suspected in patients with unexplained fever, being longer than 2 weeks, pallor, splenomegaly, hepatomegly and potential exposure in an endemic area or from areas from where On complete blood count (CBC), the majority of patients had anemia, leucopenia, and thrombocytopenia (90%, 67.5% and 72.5%, respectively) followed by neutropenia (27.5%), and lymphocytosis (65%). Similar finding were observed by various authors such as Dash S et al 7 , Singh K et al, 12 and Petrela R et al 20 series have reported a normocytic normochromic anemia in peripheral smear examination. 11,13,14 In this study we observed normocytic normochromic and anisocytosis hypochromic in equal frequency (35%) followed by anisopoikilocytosis hypochromia (20%), normocytic hypochromia (5%) and anisopoikilocytosis normochromic (2.5%).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Positive findings like pallor, splenomegaly, hepatomegaly were observed but less common than to the Dash S et al 7 and Hamid GA et al 18 Visceral leishmaniasis should be strongly suspected in patients with unexplained fever, being longer than 2 weeks, pallor, splenomegaly, hepatomegly and potential exposure in an endemic area or from areas from where On complete blood count (CBC), the majority of patients had anemia, leucopenia, and thrombocytopenia (90%, 67.5% and 72.5%, respectively) followed by neutropenia (27.5%), and lymphocytosis (65%). Similar finding were observed by various authors such as Dash S et al 7 , Singh K et al, 12 and Petrela R et al 20 series have reported a normocytic normochromic anemia in peripheral smear examination. 11,13,14 In this study we observed normocytic normochromic and anisocytosis hypochromic in equal frequency (35%) followed by anisopoikilocytosis hypochromia (20%), normocytic hypochromia (5%) and anisopoikilocytosis normochromic (2.5%).…”
Section: Discussionsupporting
confidence: 89%
“…The majority of cases of kala azar seen in our study were from Eastern Nepal such as Morang, Sunsari and Saptari. Similar study was done by Singh K et al 12 The condition affects the poorest of the poor section of people residing in this part of Nepal. Concentrated cases lie nearby to BPKIHS which is not an accidental finding as BPKIHS is only the treatment centre in Eastern reagion hence cases from Eastern district are least likely to be missed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…3 In the Indian form, caused by L. d. donovanum, man appears to be the main reservoir and the incidence is high in children aged 5-10 years and young adults. 4 In Oman, most cases of kala-azar come from the mountainous or rural areas in the east. Between 1972 and 1977, 61 cases of visceral leishmaniasis were diagnosed on histological demonstration of amastigotes in bone marrow and, between 1978 and 1998, 240 patients were reported nationally.…”
Section: Introductionmentioning
confidence: 99%